LEBY LAYERS OF NAMES USED IN THE ARTISTIC WORKS OF TAHIR MALIK - Hamroyeva , Maftuna Rasulovna (Innovative Development in Educational Activities, 2023)
This article discusses the lexical layers of human names, which are one of the anthroponymic units of the writer’s style, the importance of their use in the creative style, their place in the language. Opinions on the use of anthroponymic forms in the works of the writer are also revealed through examples.